Bilateral clear lens extraction and intraocular lens implantation in a child with microspherophakia and Marfan syndrome - Farat, Joyce Godoy [UNESP]; Nascimento Queiroz, Marjorie Fornazier [UNESP]; Lottelli, Antonio Carlos [UNESP] (Consel Brasil Oftalmologia, 2019)
We report the case of a 4-year-old boy with Marfan syndrome whose parents reported he had had low visual acuity since birth. On examination, there was microspherophakia and a small subluxation of the lens. The objective refraction was -23.75 - 2.75 x 70 in the right eye and -25.50 -3.50 x 90 in the left eye. Since the microspherophakia and the high myopia severely affected the boy's quality of life, clear lens extraction, anterior vitrectomy, posterior surgical capsulotomy via the pars plana, and intraocular lens implantation were performed. Two years postoperatively, the patient had centered intraocular lenses and a corrected visual acuity of 20/30 in both eyes. The child was satisfied with his vision and was able to study and perform daily activities without visual limitations.
Keywords: Marfan syndrome; Lens, intraocular; Lens implantation, intraocular; Lens, crystalline/surgery; Visual acuity; Humans; Child, preschool; Case reports